Comparison of iRoot BP Plus and mineral trioxide aggregate for pulpotomy in primary molars under general anesthesia: a 3-year retrospective study - Yiming Zhao; Yuyan Tao; Yan Wang; Jing Zou; Qiong Zhang (PeerJ)
Background Pulpotomy is a widely recommended treatment for deep caries and reversible pulpitis in primary teeth. However, there is a significant lack of large-scale clinical studies evaluating the long-term efficacy of pulpotomy in primary molars, especially in studies with follow-up periods extending beyond a two years. Aim This study aimed to evaluate the long-term efficacy of mineral trioxide aggregate (MTA) and iRoot BP Plus for pulpotomy in primary molars performed under general anesthesia and to investigate factors influencing the success rate. Methods In this retrospective study, a total of 942 primary molars from 422 children who met the inclusion criteria underwent pulpotomy. Propensity score matching method (PSM) was used to match the MTA and iRoot BP Plus groups in a 1:1 ratio based on covariates. Efficacy was assessed using the Zurn & Seale criteria. Kaplan-Meier survival analysis and Cox proportional hazards model were performed to analyze the outcomes. Results PSM resulted in 266 pairs of matched teeth from 532 teeth of 291 children (mean age: 4.64 ± 1.07 years, ranging from 2 to 8 years). Long-term clinical and radiographic evaluations revealed higher success rates for iRoot BP Plus (24-month: 99.54%/97.25%; 36-month: 97.22%/95.83%) compared to MTA (24-month: 94.76%/95.29%; 36-month: 92.50%/91.25%). Survival analysis indicated a statistically significant difference between two groups (P = 0.0042). Age, gender, tooth position, and decayed tooth surface showed no significant impact on pulpotomy success, whereas the choice of pulp capping materials significantly influenced the outcome (HR [95% CI]=0.3745[0.1857-0.7552], P = 0.006). Conclusion Clinical and radiographic evaluations support the use of iRoot BP Plus for pulpotomy in primary molars.